Aplikasi Penjadwalan Dan Monitoring Terapi Anak Dengan Autisme Berbasis Android Menggunakan Metode RUP (Rational Unified Proces) - I Putu Gede Abdi Sudiatmika; A A Raka Jayaningsih; Rifky Lana Rahardian; Komang Hari Santhi Dewi (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Currently, the trend is that the number of children with autism spectrum disorders (autism) is growing in Indonesia is showing an increasing number and a wider spread, not only in urban areas but also in villages and remote areas. Early and intensive treatment and choosing the right method will make a difference for children with autism to achieve behavior that is appropriate to the child's age. The method of handling autistic children is often called an intervention or a treatment that is repeated. Intervention or therapy is carried out at a child autism center or service. Based on the research team's search for autism service centers (PLA), there are approximately 20 autism and disability service centers in Denpasar. Autism service centers usually have therapy services including speech therapy, occupational therapy, physiotherapy, and aquatic therapy. At this time, the use of smartphones has become a way of life for almost all levels of society. People are used to using Android smartphones to communicate through social media. In general, these smartphones have not been utilized optimally for productive activities. This research will discuss an Android-based application that was developed to assist administration services to PLA in the form of data collection on children with autism. The system development method used is the RUP (Rational Unified Process) method. RUP is a software engineering method developed by collecting various best practices in the software development industry. The system to be built has 2 actors, namely the PLA admin and parents as users. The PLA admin is in charge of managing administration such as child data, therapy data, therapy schedules and history of therapy results. Based on the calculation results from the Likert scale, the authors conclude that the level of user satisfaction in terms of benefits ranges from 88.5% which is in the satisfied category, in terms of effectiveness it is obtained 91.1% which is in the very satisfied category, in terms of interface it is obtained 86.5% which is in the very category satisfied and in terms of content, it was found that 89% were in the very satisfied category.